Hubungan Penerimaan Diri dengan Kepatuhan Pembatasan Cairan pada Pasien Gagal Ginjal - Ana Khumaeroh; Lestari Sukmarini; Masfuri Masfuri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to identify the relationship between self acceptance and fluid adherence in ESRD patients undergoing HD. This study used cross sectional design with consecutive sampling of 121 respondents. Data collection used fluid adherence questionnaires, self acceptance scale and documentation studies. The analysis used chi square and logistic regression. The result showed that 79,3% of respondents had adherence to fluid restriction and 78,5% of them had self acceptance. The analysis result also showed there was a significant relationship between self acceptance and fluid adherence (p=0,024), but no significant relationship between self-acceptance and IDWG (p=0.154). There was significant relationship between confounding variable of the length of time undergoing HD and fluid adherence (p=0.033), adequacy HD and IDWG (p=0,011). However, other confounding variables were not significant relationship with fluid adherence, which were: age, gender, education, and comorbidities. Furthermore, the multivariat analysis found that self acceptance was the most dominant variable affecting fluid adherence (p=0.006) after controlling by variables of the sex and the length of time undergoing HD, which can predicted 21% to fluid adherence. In conclusion, from the results of this study, it was found that there was a significant relationship between self-acceptance and length of time undergoing hemodialysis with fluid adherence in terminal renal failure patients undergoing hemodialysis. Key words: Hemodialysis, End Stage Renal Disease, Fluid adherence, Self Acceptance